Comparison Of Capital Structure, Profitability, And Third-Party Funds (DPK) Between Bank Bri And Bank Syariah Indonesia: A Comparative Analysis - Dayanti, Mahesa (Al-Kharaj: Journal of Islamic Economic and Business, 2024)
The banking sector plays a crucial role in the Indonesian economy, becoming the backbone that supports the country's economic growth and stability. In this dynamic landscape, two financial institutions stand out, namely Bank Rakyat Indonesia (BRI) as a representative of conventional banks, and Bank Syariah Indonesia (BSI) which is committed to Islamic financial principles. The purpose of this study is to determine the comparison of capital structure, profitability, and third party funds (DPK) between BRI banks and Indonesian Islamic banks. This research method uses the Mixed Methods Comparative method, this approach involves the collection and analysis of quantitative and qualitative data separately and at the same stage. The results of this study show that the comparative analysis between Bank BRI and Bank Syariah Indonesia (BSI) highlights the different dynamics in the capital structure, profitability, and deposits of both. BRI, with its conventional approach, demonstrates flexibility and excellence in diversifying financial resources. On the other hand, BSI, as an Islamic bank, provides evidence that Islamic principles can provide profitability and a sustainable financial foundation. These results provide a better understanding of each bank's role in meeting the needs of society, both in terms of financial services and business ethics principles. Stakeholders, including regulators, investors, and the general public, can use the results of this analysis to make informed decisions and support the sustainable growth of the banking sector in Indonesia.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//